2009
DOI: 10.1123/jsep.31.4.505
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating the Black Box: Investigating Prefrontal Cortical Hemodynamics during Exercise with Near-Infrared Spectroscopy

Abstract: Near-infrared spectroscopy (NIRS) presents an appealing option for investigating hemodynamic changes in the cerebral cortex during exercise. This review examines the physical basis of NIRS and the types of available instruments. Emphasis is placed on the physiological interpretation of NIRS signals. Theories from affective neuroscience and exercise psychobiology, including Davidson's prefrontal asymmetry hypothesis, Dietrich's transient hypofrontality hypothesis, and Ekkekakis's dual-mode model, are reviewed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
171
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(179 citation statements)
references
References 166 publications
(227 reference statements)
0
171
1
3
Order By: Relevance
“…Exercise cerebral oxygenation (Cox) (as noninvasively determined by nearinfrared spectroscopy) depends upon the dynamic balance between the instantaneous rate of oxygen delivery and oxygen utilisation [3]. KOIKE et al [4], for instance, reported that congestive heart failure (CHF) HFrEF was associated with appreciable decreases in COx during exertion.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Exercise cerebral oxygenation (Cox) (as noninvasively determined by nearinfrared spectroscopy) depends upon the dynamic balance between the instantaneous rate of oxygen delivery and oxygen utilisation [3]. KOIKE et al [4], for instance, reported that congestive heart failure (CHF) HFrEF was associated with appreciable decreases in COx during exertion.…”
Section: To the Editormentioning
confidence: 99%
“…Indeed, mean arterial pressure, a major determinant of cerebral blood flow [8], was reduced throughout the exercise tests and related to COx in COPD+HFrEF. Slight impairments in mean arterial pressure might reduce cerebral blood flow, particularly in the presence of impaired autoregulation and excessive sympathetic drive [3,8]. There is also some evidence that decreased cardiac output may impair exercise COx, independent of mean arterial pressure [8].…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The NIRS allows quantification of oxyhemoglobin (O 2 Hb), deoxyhemoglobin (HbH) and total hemoglobin (HbT) according to absorbance at specific wavelengths (Ekkekakis, 2009). We used O 2 Hb since it is the best indicator of cerebral blood flow changes, according to Hoshi and colleagues (Hoshi, Kobayashi, & Tamura, 2001).…”
Section: Near-infrared Spectroscopy (Nirs)mentioning
confidence: 99%
“…The amplitudes of changes in oxy and deoxyhaemoglobin within the motor cortex areas have been shown to be dependent on the force production: the stronger the push, the higher the oxyhaemoglobin (Shibuya and Tachi, 2006;Smith et al, 2003). However, at low levels of force, there might be no detection by the NIRS systems (at least 10% of maximal voluntary contraction needed); while at high levels (about 50% of maximal voluntary contraction and above) there might be no plateau but only a peak in oxyhaemoglobin (Ekkekakis, 2009). This type of activation pattern is valid only for steady systemic variables (ie.…”
Section: Patternsmentioning
confidence: 99%